Efeitos do uso do equipamento de proteção no comportamento autolesivo em adolescente com diagnóstico de TEA - Brasil, Giovana Azevedo Reolon (2019)
The main objective of this study was to identify the antecedent and consequent events of the self-injurious behavior of a teenager with atypical development. A second objective was to evaluate the effects of the protective equipment use on the functional analysis and intervention of these behaviors. To achieve this, it was used indirect functional assessments as strategies through interviews with professionals and family members, direct functional observation at the participant's institution and at home, and functional analysis with five conditions: attention, tangible, demand, alone and control. All conditions were controlled by multiple element design, with and without the use of protective equipment. During the intervention in self-injurious behavior, it was used the ABAB design succeeded by follow-up, where the use of helmet was manipulated. The results suggest that selfinjurious behavior was maintained by positive reinforcement, which means, for access to items and social attention. The use of protective equipment produced a suppressive effect on the response. Thus, it is discussed that its use is not recommended during the functional analysis procedure, as it may mask the results, but may be a part of an intervention that aims changing the contingency responsible for maintaining the response.